Сравнительная характеристика традиционного проектирования и BIM-технологий - Волынец, Д. М.; Булло, Л. М. (БНТУ, 2022)
Comparative characteristics of CAD and BIM design methods: project data, incoming data, compliance of the object with the project, administrative issues. Advantages of parametric design in a BIM system.